Incidence of Dengue Virus Types in Mosquito Population from Urban, Peri-urban and Rural Settings of Jodhpur, Rajasthan to Predict the Risk of Dengue Hemorrhagic Fever - Rashmi Chouhan; Bennet Angel; Annette Angel; Vinod Joshi (Journal of Pure and Applied Microbiology)
Dengue Fever and Dengue Hemorrhagic Fever (DHF) stands as the principal cause of prolonged illness and death among individuals of all age groups. The screening of mosquitoes from risk areas and the identification of virus types present can offer crucial epidemiological insights regarding the potential risk of DHF. Therefore, to prove this an investigation was carried out on various dengue virus types present within field-collected Aedes mosquitoes in the urban, rural and peri-urban areas of Jodhpur, Rajasthan, India. Adult Aedes mosquitoes were captured from human residences and outskirts. Individual mosquitoes were subjected to Indirect Fluorescence Antibody Test (IFAT). The virus isolation studies from the Aedes aegypti of peri-urban foci of Jodhpur district have shown maximum presence of DEN-1 and DEN-3 types and none of the mosquitoes positive for DEN-4. On the other hand, from the same settings Aedes vittatus showed DEN-1, 2 and 3 in maximum proportion whereas, DEN-4 virus type, like Aedes aegypti, showed least presence in Aedes vittatus mosquitoes also. Samples combined for all the settings showed that of total 450 mosquitoes screened for dengue antigens, the maximum percentage (36.6%) of DEN-3 type was observed followed by DEN-2 (28.5%), DEN-1 (18.7%) and least in the case of DEN-4 (16.0%). In the arid regions of Jodhpur, where people tend to store domestic water excessively and for extended periods, current findings regarding the presence of all four types of dengue viruses could significantly impact the understanding the risk factors associated with the occurrence of DHF in the area.